2019
DOI: 10.1101/724203
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maximizing Ecosystem Services Provided to the New Oil Crop Brassica carinata Through Landscape and Arthropod Diversity

Abstract: 21 tilling, or bee hives. Increased heterogeneity could save farmers from the input cost of treatment 45 or tillage, by way of increased insect diversity, while still providing similar yields. 46 47 SUPPLEMENTARY MATERIALS HAVE NOT BEEN INCLUDED WITH THIS TEXT 48 49

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Landscape‐level analyses matter not only for ecological outcomes but also for the formulation of best farming practices. For example, Stiles et al (2021) demonstrated that increased landscape diversity (measured as Shannon's diversity index with land use quantified in CropScape) in the South Dakota Prairie Coteau (a roughly 50,000‐km 2 plateau that rises from the flat prairies of western Minnesota and eastern South Dakota) resulted in higher pollinator diversity and higher yield in experimental plots of the new oil crop, Brassica carinata . Thus, landscape‐level management that increases pollinator diversity could increase farmers' net profitability by replacing costs associated with inputs such as tillage and neonicotinoid seed treatments.…”
Section: Resources For Pollinators An Exemplar Approachmentioning
confidence: 99%
“…Landscape‐level analyses matter not only for ecological outcomes but also for the formulation of best farming practices. For example, Stiles et al (2021) demonstrated that increased landscape diversity (measured as Shannon's diversity index with land use quantified in CropScape) in the South Dakota Prairie Coteau (a roughly 50,000‐km 2 plateau that rises from the flat prairies of western Minnesota and eastern South Dakota) resulted in higher pollinator diversity and higher yield in experimental plots of the new oil crop, Brassica carinata . Thus, landscape‐level management that increases pollinator diversity could increase farmers' net profitability by replacing costs associated with inputs such as tillage and neonicotinoid seed treatments.…”
Section: Resources For Pollinators An Exemplar Approachmentioning
confidence: 99%
“…Moreover, carinata has a moderate weed risk potential (US Department of Agriculture – Animal & Plant Health Inspection Service, 2014) with its low pod‐shattering and dormancy (Patanè & Tringali, 2011). It supports over 50 species of pollinators and 75 species of non‐pollinators, thereby providing biodiversity benefits (Stiles, 2019).…”
Section: Carinata To Address the Demand For A Low‐carbon Bioeconomymentioning
confidence: 99%
“…Other insects, such as butterflies, flies and wasps also forage on Brassica flowers, but their contribution to boosting yields is negligible (Mishra et al 1988;Pudasaini et al 2015;Bajiya and Abrol 2017;Stanley et al 2017). The diversity of these insects within such crops may be raised if attributes such as restricted use of pesticides, wide availability of food and nesting resources and large-scale landscape (3 km) heterogeneity are present in these areas (Samnegård et al 2016;Landaverde-González et al 2017;Theodorou et al 2017;Stiles et al 2019).…”
Section: Introductionmentioning
confidence: 99%